1982
DOI: 10.1677/joe.0.0940347
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin secretion and dopamine receptors of the MtTW15 transplantable pituitary tumour

Abstract: The MtTW15 transplantable pituitary tumour grown in rats was tested in vitro for the ability of dopamine agonists to affect prolactin secretion and for the existence of dopamine receptors. Prolactin release from enzymatically dispersed cells and non-enzymatically treated tissue fragments of both the tumour and the anterior pituitary gland was determined in a cell perifusion column apparatus. Dopamine (0·1–5 μmol/l), bromocriptine (50 nmol/l) and the dopamine antagonist haloperidol (100 nmol/l) had no effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Some mixed PRL-secreting transplantable pituitary tumors such as the 7315a and the MtTW15, although containing high-affinity D2 receptors (Cronin et al, 1981(Cronin et al, , 1982, are refractory to dopaminergic inhibition of PRL release (Lamberts and MacLeod, 1979). Although no clear-cut explanation has yet been offered for such a phenomenon, recent data obtained in our laboratory suggest that it may be due to the presence in both tumors of significant and distinct receptorial anomalies .…”
Section: Bound or Solubilized By [3-(3-~holamidopropyl)-dimethyl-mentioning
confidence: 83%
See 1 more Smart Citation
“…Some mixed PRL-secreting transplantable pituitary tumors such as the 7315a and the MtTW15, although containing high-affinity D2 receptors (Cronin et al, 1981(Cronin et al, , 1982, are refractory to dopaminergic inhibition of PRL release (Lamberts and MacLeod, 1979). Although no clear-cut explanation has yet been offered for such a phenomenon, recent data obtained in our laboratory suggest that it may be due to the presence in both tumors of significant and distinct receptorial anomalies .…”
Section: Bound or Solubilized By [3-(3-~holamidopropyl)-dimethyl-mentioning
confidence: 83%
“…Adult Buffalo and Wistar-Furth female rats (Harlan Sprague-Dawley, Indianapolis, IN, U.S.A.), 180 g of body weight, were inoculated subcutaneously with a mince of 73 15a and MtTW 15 tumor, respectively. These transplantable tumors have been carried in rats since the early 1960s (Cronin et al, 1981(Cronin et al, , 1982. Animals were housed under controlled conditions of light (1 2 h of light starting at 0600 h) and temperature (22°C) and fed water and rat pellets ad libitum.…”
Section: Animals and Tumor Productionmentioning
confidence: 99%
“…Because these tumors have the same dopamine-binding characteristics as those of normal tissue (37,38), the tissue may have a postreceptor defect that is responsible for its lack of biological responsiveness. It was important to determine whether phospholipid turnover in pituitary tumor 7315a, which secretes large amounts of PRL and only a small amount of ACTH (39), is affected by dopamine.…”
Section: Effect Ofdopamine On 32 P Incorporation Into Phospholipids Imentioning
confidence: 99%
“…therefore, different from the tumors in our study. Another PRL/GH-secreting tumor line (MtT.WI5), possessing dopamine receptors and found to be refractory to the effects of BEC treatment, showed no decrease in blood PRL levels or tumor growth [7], There are several factors which complicate the assess ment of the results of this study. Not all old female LongEvans rats develop PRL-containing adenomas, and not all of those which do occur are sparsely granulated.…”
Section: Discussionmentioning
confidence: 76%
“…Several workers have reported that BEC fails to reduce circulaling PRL. lev els in rats bearing certain transplanted pituitary tumors [7,8,23] as well as PRL release from dispersed pituitary tumor cells [9]. The GH.i cell line apparently lacks dopamine re ceptors [6], and BEC does not inhibit PRL release from these cells [I I], However, it must be noted that the origin of the GH?…”
Section: Discussionmentioning
confidence: 99%